POWER, THE RISK PROPENSITY, INNOVATION SYSTEMS TO THE DECISION MAKING OF THE PRINCIPALS SENIOR HIGH SCHOOL ACCREDITED "A" DKI JAKARTA 2017 - Muljani, Raden Heni (Journal of Education Research in Administration and Management (JERAM), 2017)
The research objectives was to study the effect of power, the propensity for risk, and innovation systems to the decision making of the principals of senior high school accredited â€œAâ€ DKI Jakarta. The research method used quantitative approach with survey method. The samples research were 148 principals of senior high school as respondents who were selected through simple random sampling. Process for the research result has been used path analysis. The result of the research can be concluded (1) there was a positive direct effect of power to decision making, (2) there was a positive direct effect of propensity for risk to decision making, (3) there was a positive direct effect of the innovation systems to decision making, (4) there was a positive direct effect of the power to the innovation systems and (5) there was a positive direct effect of risk propensity to innovation systems. Therefore, variations in the principal's decision making is influenced by variations of power, the propensity for risk, and innovation systems.